2013
DOI: 10.1007/s11548-013-0953-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of novice reader diagnostic performance in coronary CT angiography using an advanced cardiac software package

Abstract: PurposeThe purpose of this research was to evaluate whether a commercially available advanced cardiac software package for coronary CT angiography (CTA) interpretation may reliably assist inexperienced readers to screen for significant coronary artery stenoses.MethodsCoronary CTA data sets of 61 consecutive patients with suspected coronary artery disease were evaluated by three novice readers with no experience in cardiac CT interpretation. In the first 15 patients, the novice readers were trained to use the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Correct interpretation of cardiac imaging requires extensive training and experience, needed to reduce inter-observer variability [ 21 ]. Inexperienced readers, at the beginning of their learning curve, benefit from the assistance of dedicated software in the identification of coronary arteries and segments [ 17 , 22 , 23 ]. A thorough evaluation of the coronary tree is fundamental for the CCTA to achieve high diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correct interpretation of cardiac imaging requires extensive training and experience, needed to reduce inter-observer variability [ 21 ]. Inexperienced readers, at the beginning of their learning curve, benefit from the assistance of dedicated software in the identification of coronary arteries and segments [ 17 , 22 , 23 ]. A thorough evaluation of the coronary tree is fundamental for the CCTA to achieve high diagnostic yield.…”
Section: Discussionmentioning
confidence: 99%
“…The application of such tools are more convenient than semi-automated methods and may theoretically further facilitate coronary vessels’ evaluation, favoring the trend towards less reader dependency [ 15 ]. It has been demonstrated that advanced cardiac software packages have a NPV similar to high experience readers while their positive predictive value is comparable to novice CCTA readers [ 16 ]; additionally, they may assist novice readers in ruling out significant CAD [ 17 ]. Nevertheless, to the best of our knowledge, previous investigations were focused on diagnostic performances rather than the identification of coronary vessels and segments as an aiding tool for inexperienced CCTA readers.…”
Section: Introductionmentioning
confidence: 99%
“…In the present however, AI-like CAD systems are only used as a supplementary aid for the radiologists' subjective image assessment [19]. Therefore, the performance of CADs is depending on the users' knowledge and experience and has been shown to successfully assist even novice readers [20]. Regarding ILDs, while CADs have shown promising results such as good accuracy in detecting fibrosis on a quantitative level [21] and good performance in distinguishing between specific diseases such as UIP and non-specific interstitial pneumonia (NSIP) [22], current systems are usually limited in the number of different ILDs they comprise of and patterns they recognize.…”
Section: Introductionmentioning
confidence: 99%